Influence of FaÃ§ade Configuration on Thermal Performance of Residential Unit of Typical Walk-up Flats in Surabaya - Nurdin, Apriliana Hidayati; Antaryama, I Gusti Ngurah; Ekasiwi, Sri Nastiti Nungrahani (IPTEK Journal of Proceedings Series, 2020)
Flat design has evolved and taken many shapes and forms. Most of the arrangements are arranged in a double-load layout where the units are positioned face to face along the corridor. Another type is two single-loaded flats that are configured to face the courtyard. Building faÃ§ade also varies from those with shaded surfaces to those with minimum sun protection. Modification in design clearly has an impact on the thermal performance of the buildings. The aim of the study is to investigate the facade configuration on the thermal performance of the building. This study uses simulation software, namely, Design Builder, to predict the thermal performance of the buildings. Several variants of window areas, sun shading, balconies are arranged to explore their effects on thermal performance. Flat with yard selected as a reference model. The results showed that the smaller the window area and the greater coverage given to the window with a shading device, combined with the balcony, can provide a decrease in air temperature up to 0.57 â°C, with a reduction in cooling degree hours percentage of 36.97% comparing to the reference model.